Surgical strategy for pediatric liver tumors involving the hepatic venous confluence and the inferior vena cava - Fuchs, Juri; Rabaux-Eygasier, Lucas; Hery, Geraldine; Fouquet, Virginie; Guerin, Florent; Franchi-Abella, Stephanie; Branchereau, Sophie (Annals of surgical oncology, 2025)
BACKGROUND: Pediatric liver tumors presenting as centrally located masses with contact to or even invasion of all three hepatic veins (HVs) and the inferior vena cava (IVC) present significant surgical challenges. While liver transplantation may be indicated in truly unresectable tumors, extended liver resection with vascular reconstruction can be an organ-preserving alternative. - OBJECTIVE: This study aimed to present a reference center's strategy for children with liver tumors involving the hepatic venous confluence or the retrohepatic IVC who underwent extended liver resection with vascular reconstruction. - METHODS: All pediatric patients undergoing major hepatectomy with reconstruction of an HV or the IVC over a 10-year study period were included. Preoperative imaging, surgical techniques, and short- and long-term postoperative data were analyzed. - RESULTS: From a total of 125 pediatric major hepatectomies, 17 children (15 hepatoblastoma, two undifferentiated embryonal sarcoma) underwent liver resection with vascular reconstruction of an HV or the IVC. In nine cases an HV was reconstructed, and in eight children, a partial resection of the IVC was performed. Total vascular exclusion of the liver was applied in 16/17 cases. No 90-day postoperative mortality, no major postoperative complication, and no local relapse occurred; 16/17 patients are alive without relapse at a median follow-up of 44 months (range 19-111). - CONCLUSION: This is the largest single-center series to report major hepatectomies with HV or IVC reconstruction in children. In specialized centers, these complex procedures are associated with excellent outcomes. Successful tumor resection can be achieved in selected cases even in locally advanced tumor stages.